Design and simulation of 2x2 MMI coupler and thermo-optic switch using sol-gel derived organic-inorganic hybrid material - A. Samah, M. Firdaus (American Institute of Physics, 2011)
A new design of Multimode Interference (MMI) thermo-optic switch with improved crosstalk figure is demonstrated in this paper. The device is designed and simulated using BeamProp 3D from Rsoft and 3D BPM CAD softwares. The devices are designed based on sol-gel derived organic-inorganic hybrid material, vinyltriethoxysilane (VTES), tetraethoxysilane (TEOS) and tetrabutoxytitanate (TTBu) or VTT with refractive index of 1.47 as a core and surrounded by silica with refractive index of 1.45 at 1550 nm wavelength. The switching power is 164mW and the simulation result show that the propagation loss of the MMI device is 1.8 dB and zero crosstalk.